The role of Ti and TiC nanoprecipitates in radiation resistant austenitic steel: A nanoscale study - Cautaerts, Niels; Delville, Rémi; Stergar, Erich; Pakarinen, Janne; Verwerft, Marc; Yang, Yong; Hofer, Christina; Schnitzer, Ronald; Lamm, Steffen; Felfer, Peter; Schryvers, Dominique (Acta Materialia, 2020)
This work encompasses an in-depth transmission electron microscopy and atom probe tomography study of Ti-stabilized austenitic steel irradiated with Fe-ions. The focus is on radiation induced segregation and precipitation, and in particular on how Ti and TiC affect these processes. A 15-15Ti steel (grade: DIN 1.4970) in two thermo-mechanical states (cold-worked and aged) was irradiated at different temperatures up to a dose of 40 dpa. At low irradiation temperatures, the cold-worked and aged materials evolved to a similar microstructure dominated by small Si and Ni clusters, corresponding to segregation to small point defect clusters. TiC precipitates, initially present in the aged material, were found to be unstable under these irradiation conditions. Elevated irradiation temperatures resulted in the nucleation of nanometer sized Cr enriched TiC precipitates surrounded by Si and Ni enriched shells. In addition, nanometer sized Ti- and Mn-enriched G-phase (M6Ni16Si7) precipitates formed, often attached to TiC precipitates. Post irradiation, larger number densities of TiC were observed in the cold-worked material compared to the aged material. This was correlated with a lower volume fraction of G-phase. The findings suggest that at elevated irradiation temperatures, the precipitate-matrix interface is an important point defect sink and contributes to the improved radiation resistance of this material. The study is a first of its kind on stabilized steel and demonstrates the significance of the small Ti addition to the evolution of the microstructure under irradiation.
CRIS-Team Scopus Importer:2020-08-07
Keywords: APT; Austenitic steel; G-phase; Precipitation; Radiation induced segregation; TEM; TiC